Synthesis and Anti‐Oomycete Activity of 1‐Sulfonyloxy/Acyloxydihydroeugenol Derivatives. Issue 9 (4th August 2021) - Chen, Genqiang; Zhu, Lina; He, Jiaxuan; Zhang, Song; Li, Yuanhao; Guo, Xiaolong; Sun, Di; Tian, Yuee; Liu, Shengming; Huang, Xiaobo; Che, Zhiping
Abstract: Endeavor to discover biorational natural products‐based fungicides, two series (26) of novel 1‐sulfonyloxy/acyloxydihydroeugenol derivatives (3a –p and 5a –j ) were prepared and assessed for their fungicidal activity against P. capsici Leonian, in vitro . Results of fungicidal activity revealed that, among all compounds, especially compounds 3a, 5c, and 5e displayed the most potent anti‐oomycete activity against P. capsici with EC50 values of 69.33, 68.81, and 67.77 mg/L, respectively. Overall, the anti‐oomycete activities of 1‐acyloxydihydroeugenol derivatives (5a –j ) were higher than that of 1‐sulfonyloxydihydroeugenol derivatives (3a –p ). It is proved that the introduction of the acyl group at hydroxy position of dihydroeugenol is more beneficial to improve its anti‐oomycete activity than that of the sulfonyl group. These preliminary results will pave the way for further modification of dihydroeugenol in the development of potential new fungicides. Abstract :